2021
DOI: 10.1155/2021/8538188
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review on Wild-Edible Fruit Species in Ethiopia

Abstract: Wild edible fruit species are commonly consumed and utilized in different parts of Ethiopia for staple food, filling seasonal food shortages, emergency food during a famine, and household income generation. There is a pressing need for domestication and improvement of some wild edible fruits for increased production, diversifying income for small-scale farmers, and conservation of the diminishing wild edible fruit resources. A total of 37 widely utilized and marketed wild edible fruit species falling into 23 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In Zimbabwe, many households rely on wild fruits as a source of food for nearly a quarter of the dry seasons (Kidane and Kejela, 2021). This is similar to trends seen in Ethiopia, where wild fruits are consumed to withstand seasonal shortage of food (Melaku and Ebrahim, 2021). In contrast to this, in Uganda most wild fruits are gathered during the rainy season (Nyero et al, 2021).…”
Section: Living Under Extreme Conditions: Some Adaptation Strategiesmentioning
confidence: 79%
See 1 more Smart Citation
“…In Zimbabwe, many households rely on wild fruits as a source of food for nearly a quarter of the dry seasons (Kidane and Kejela, 2021). This is similar to trends seen in Ethiopia, where wild fruits are consumed to withstand seasonal shortage of food (Melaku and Ebrahim, 2021). In contrast to this, in Uganda most wild fruits are gathered during the rainy season (Nyero et al, 2021).…”
Section: Living Under Extreme Conditions: Some Adaptation Strategiesmentioning
confidence: 79%
“…Under extreme conditions, local communities usually adopt various measures, so as to cope with their impacts (Debela et al, 2019). These may include income diversification by growing different cash and food crops, feeding animals with crop residues and tree branches, utilization of hay for animals feed, and the gathering and consumption of wild fruits and vegetables as food items (Coppock, 1994;Abdulla, 2013;Birhanu et al, 2017;Melaku and Ebrahim, 2021). Table 1 outlines some examples of plants being used in various ways, as part of the adaptation strategies implemented by various communities in an attempt to cope with extreme events.…”
Section: Living Under Extreme Conditions: Some Adaptation Strategiesmentioning
confidence: 99%
“…A critical review of wild edible species of Ethiopia found a lack of scientifically based information about a key range of genetic variables important for tree domestication which has resulted in a failure to capture their full potential in terms of quality, production, and marketing [452].…”
Section: Highlands and Drylands Of East Africa 71 State Of Natural Re...mentioning
confidence: 99%
“…Adansonia digitata L., Tamarindus indica L., and Ziziphus mauritiana Lam. are some of the underutilized species in Ethiopia [14]. Tis study therefore flls the gaps by identifying households' expectations, conventional expertise, management problems, and consumption of edible woody plants in the study area.…”
Section: Introductionmentioning
confidence: 99%